2019
DOI: 10.3390/medicina55060302
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Canonical TGF-β Signaling in Urothelial Bladder Cancer

Abstract: Background and objectives: Dysregulation of TGF-β signaling plays multiple roles in cancer development and progression. In the canonical TGF-β pathway, TGF-β regulates the expression of hundreds of target genes via interaction with Smads, signal transducers and transcriptional modulators. We evaluated the association of TGF-β1, Smad2, and Smad4, the key components of canonical TGFβ pathway, with clinicopathologic characteristics of urothelial bladder cancer, and assessed their prognostic value in prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“… 71 72 It is also a key inducer and regulator of EMT, an essential process for cancer progression and metastatic spread. 53 73 TGF-β expression is an independent predictor of outcomes in urothelial cancer, 74 but this association had not been demonstrated thus far in gastric cancer. Our study demonstrated that a high TGF-β fibrosis gene signature is negatively associated with survival in gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“… 71 72 It is also a key inducer and regulator of EMT, an essential process for cancer progression and metastatic spread. 53 73 TGF-β expression is an independent predictor of outcomes in urothelial cancer, 74 but this association had not been demonstrated thus far in gastric cancer. Our study demonstrated that a high TGF-β fibrosis gene signature is negatively associated with survival in gastric cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies focusing on the prognostic prediction of TGF-b have been published. Slavica Stojnev et al evaluated the associations of TGF-b1, Smad4, and Smad2 with clinicopathologic characteristics and prognosis in urothelial bladder cancer (25). We compared our work with these previous works.…”
Section: Discussionmentioning
confidence: 99%
“…The construction and validation of scoring models has been a core of ceaseless studies in oncology research. Numerous risk models related to EMT, immune TME, and hypoxia have been lucubrated and reported with the potential to predict prognosis and guide precision medicine for BLCA (23,25,(65)(66)(67)(68). It was remarkable that our previous work clarified thought in screening key genes, constructing a gene model, associating the model with immune characteristics, and evaluating the accuracy for predicting prognosis and treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumors with high TLR4 expression have low infiltrated levels of plasma cells, M0 macrophages, and M1 macrophages with activated TGF-β and apoptosis pathways. High expression of Smad2 and Smad4 in the TGF-β signaling pathway predicts longer OS in bladder cancer patients, while TGF-β1 is inversely correlated with the survival rate (Stojnev et al, 2019). BCG can stimulate TLR2/4 in bladder tumor cells to decrease cell proliferation and up-regulate apoptosis (Camargo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%